Предмет: Алгебра,
автор: strrran
Упростите выражение
Если известно, что
Г)
Приложения:
Ответы
Автор ответа:
0
sqrt(x^2 + 4x + 4) - sqrt(x^2 - 6x + 9) = sqrt((x + 2)^2) - sqrt((x - 3)^2) = |x + 2| - |x - 3|
Если х = -7:
|-7 + 2| - |-7 - 3| = |-5| - |-10| = 5 - 10 = -5
Если х = -4:
|-4 + 2| - |-4 - 3| = |-2| - |-7| = 2 - 7 = -5
Ответ: -5
Если х = -7:
|-7 + 2| - |-7 - 3| = |-5| - |-10| = 5 - 10 = -5
Если х = -4:
|-4 + 2| - |-4 - 3| = |-2| - |-7| = 2 - 7 = -5
Ответ: -5
Похожие вопросы
Предмет: Українська мова,
автор: Shafeld43211
Предмет: Алгебра,
автор: denisbudak05
Предмет: Математика,
автор: babenvlad787
Предмет: Математика,
автор: Dctggft